AKTIVITAS FISIK, ASUPAN ENERGI DAN STATUS GIZI WANITA PEMETIK TEH DI PTPN VIII BANDUNG, JAWA BARAT - Venny Agustiani Mahardikawati; Katrin Roosita (Jurnal Gizi dan Pangan, 2008)
Quality of human resources is very important to improve productivity. The worker productivity is correlated with nutritional status and health status. The objective of the research is to analyze physical activity, energy intake, nutritional status, of women workers at Tea Plantation PTPN VIII Bandung, West Java. The cross sectional design was used in this study to elaborate physical activity, nutritional status, and productivity of tea picker’s women. The criteria of study sample were tea picker’s women at cluster area of Malabar tea plantation of PTPN VIII Bandung, having infant and they were willing to be interviewed. The total number of 92 women sample was chosen randomly. Primary data consisted of physical activity recall (2x24 hours), food consumption recall (2x24 hours), anthropometry data (weight and height), and productivity (passage of tea sprout). Secondary data were included data of PT Perkebunan Nusantara VIII Bandung, West Java. The result showed that more than a half of samples having active or moderate physical activity level (PAL). The physical activity level of samples during work day (average PAL=1.87) was higher than holiday (average PAL=1.69) (p<0.05). The physical activity was related to energy expenditure. According to Schofield equation, energy expenditure of sample during workday (average=2362 kcal) was significantly higher (p<0.05) than day off (average=2134 kcal). This result is related to Oxford equation, energy expenditure of sample during workday (average=2223 kcal) was significantly higher than holiday (average=2011 kcal). The related factors of energy expenditure are body weight and age. Energy intake on workday and day off were respectively 2362 kcal and 2134 kcal. The average energy adequacy level during workday and day off according to Schofield and Oxford equation were not significantly different, respectively 97,2% and 103,3%. The majority of samples had normal nutritional status, and 30.4% of the sample was overweight. The energy adequacy level according to Schofield and Oxford equation are related to nutritional status of women workers. Keywords: physical activity, energy expenditure, nutritional status, plantation women